Mental revolution in construction of ‘ilm tafsir and sunnah, Malaysian experience - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah; Kayati, Ruhiyah Sakinah (2016)
Islam has put a greater emphasis on the construction of ‘Ilm Tafsir and Sunnah, with Islamization and relevantization as an aim. The construction involved the process of re-evaluation of the classical method in Quran and Sunnah studies; the importance and the application of the discipline of ‘ulum al-Quran in the interpretation of the Quran, and ‘ulum al-hadith in the commentary of aḥādīth so that the interpretation of religious texts (nuṣūṣ) may provide necessary relevant and practical solutions to problem facing the Muslim society. The construction of ‘ilm tafsir and Sunnah in Malaysia is quite advanced. However both are not formally established as a discipline of science. The discussion is more towards the body of Tafsir and Sunnah itself rather than studying the problem in society from the perspective of Quran and Sunnah. This paper aims at studying the experience of Malaysia in the construction of ‘ilm tafsir and Sunnah, the historical overview and its impact towards mental revolution. This includes the establishment of religious authorities, Islamic financial system and education as a result of a long process of mental revolution. Other than presenting the success, the paper also seeks to identify the challenges and obstacles that might have hindered the progress of constructing new methodology or model of science of tafsir and the solutions to address those challenges, such as the reform of educational system, ensuring both remain as a relevant source of guidance.